Pre-hospital stroke monitoring past, present, and future: a perspective - Ben Pazi, Hilla; Jahashan, Shady; Har Nof, Sagi; Zibman, Samuel; Yanai-Kohelet, Ornit; Prigan, Limor; Intrator, Nathan; Bornstein, Natan M.; Ribo, Marc (Frontiers in Neurology, 2024)
Integrated brain-machine interface signifies a transformative advancement in neurological monitoring and intervention modalities for events such as stroke, the leading cause of disability. Historically, stroke management relied on clinical evaluation and imaging. While today's stroke landscape integrates artificial intelligence for proactive clinical decision-making, mainly in imaging and stroke detection, it depends on clinical observation for early detection. Cardiovascular monitoring and detection systems, which have become standard throughout healthcare and wellness settings, provide a model for future cerebrovascular monitoring and detection. This commentary reviews the progression of continuous stroke monitoring, spotlighting contemporary innovations and prospective avenues, and emphasizes the influential roles of cutting-edge technologies in shaping stroke care.